Plant ABC Transporters - Geisler, Markus; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This book is devoted to the fascinating superfamily of plant ATP-binding cassette (ABC) transporters and their variety of transported substrates. It highlights their exciting biological functions, covering aspects ranging from cellular detoxification, through development, to symbiosis and defense.  Moreover, it also includes a number of chapters that center on ABC transporters from non-Arabidopsis species. ABC proteins are ubiquitous, membrane-intrinsic transporters that catalyze the primary (ATP-dependent) movement of their substrates through biological membranes. Initially identified as an essential aspect of a vacuolar detoxification process, genetic work in the last decade has revealed an unexpectedly diverse variety of ABC transporter substrates, which include not only xenobiotic conjugates, but also heavy metals, lipids, terpenoids, lignols, alkaloids and organic acids. The discovery that members of the ABCB and ABCG family are involved in the movement of phytohormones has further sparked their exploration and provided a new understanding of the whole family. Accordingly, the trafficking, regulation and structure-function of ABCB-type auxin transporters are especially emphasized in this book.
ABC Transporters and Heavy Metals -- Phytate Transport by MRPs -- ABA Transport by ABCG Transporter Proteins -- Exine Export in Pollen -- Transport of Monoterpenoid Indole Alkaloids in Catharanthus roseus -- Plant Peroxisomal ABC Transporters: Flexible and Unusual -- Plastidic ABC Proteins -- ABCG Transporters and Their Role in the Biotic Stress Response -- Defence, Symbiosis and ABCG Transporters -- ABC Proteins and Other Transporters in Lotus japonicus and Glycine max -- Monocot ABC Transporters -- Structure-function of Plant ABC-transporters -- It Takes More Than Two to Tango: Regulation of Plant ABC Transporters -- Evolution of transport directionality in ABCBs -- Trafficking of ABCB-type Auxin Transporters -- Function of ABCBs in Light Signaling -- IBA Transport by PDR Proteins.
Keywords: Plant physiology; Proteins .; Plant biochemistry; Cell membranes .; Plant Physiology; Protein Science; Plant Biochemistry; Protein-Ligand Interactions; Membrane Biology